Fish parasite diversity in the Amambai river, State Mato Grosso do Sul, Brazil - Emily Soares Pereira; Juliana Rosa Carrijo Mauad; Ricardo Massato Takemoto; Sidnei Eduardo Lima-Júnior (Acta Scientiarum: Biological Sciences, 2018)
This study aimed to describe the diversity of fish parasites in the Amambai River, in the Mato Grosso do Sul State, and generate information to facilitate studies of the biotic integrity of the region. During the period of September 2015 and July 2015, 48 specimens of 11 species of fish were analyzed for parasites. A total of 56.25% of the fish sampled from the Amambai River were infected with one or more metazoan species. A total of 21,514 parasite specimens belonging to 24 different species we found; they were distributed among six groups: Acanthocephala (Neoechinorhynchida), Cestoda (Proteocephalidea), Crustacea (Ergasilidae), Digenea (Cladorchiidae, Dadaytrema), Monogenea (Dactylogyridae) and Nematoda (Atractidae, Cucullanidae, Camallanidae, Rhabdochonidae). Of these, a monogenean, Mymarothecium sp. and four nematodes – Cucullanus sp.; Procamallanus (Spirocamallanus) inopinatus Travassos, Artigas, and Pereira, 1928; Rabdochona acuminate (Molin, 1860); and Rondonia rondoni Travassos, 1920 – were recorded for the first time on new hosts. This is the first work to gather information about the parasite fauna of fish from Amambai River in the Mato Grosso do Sul State, and provides records that contribute new reports of the occurrence of parasites in new locations.